2012
DOI: 10.1063/1.4726035
|View full text |Cite
|
Sign up to set email alerts
|

Weak magnetic field-enhanced glass formation in non-ferromagnetic Al-based alloys

Abstract: We report that a transversal static magnetic field can effectively enhance glass formation of non-ferromagnetic Al-based alloys. This distinct phenomenon is mainly attributed to the Lorentz force and Joule heat generated from the magnetic field on moving alloy melts, which suppresses the diffusion of atoms and the nucleation in the alloy melts. It is anticipated that the experimental findings can provide some technical insights to the fabrication of amorphous non-ferromagnetic alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…where we proposed a new vector b = λτ q 2 B 2 ( v e + v Si ) K B T m Si , K B is the Boltzmann constant, T is absolute temperature, λ is the scaling factor. Based on the continuity equation of diffusion ∇ • J = − ∂C ∂t , we get the one-dimensional diffusion equation along the longitudinal direction of graphite tube, as indicated in equation (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where we proposed a new vector b = λτ q 2 B 2 ( v e + v Si ) K B T m Si , K B is the Boltzmann constant, T is absolute temperature, λ is the scaling factor. Based on the continuity equation of diffusion ∇ • J = − ∂C ∂t , we get the one-dimensional diffusion equation along the longitudinal direction of graphite tube, as indicated in equation (17).…”
Section: Resultsmentioning
confidence: 99%
“…With the aid of computer simulation, Zhang et al [15] have found that the atomic diffusion of the liquid can affect the solidification paths and the type/amount of phase formed during the solidification. In recent decades, the magnetic field has been considered as a powerful tool in new materials preparations [16] and crystal growth [17] or alloy solidification [18]. In addition, it is also of great importance for geophysics to investigate transport properties of the melts in the core and mantle because the heat and mass transfer of the planets' interior greatly affect the magnetic field conditions of those planets.…”
Section: Introductionmentioning
confidence: 99%
“…This was also addressed by a tracer measurement of enhanced atomic diffusion in a shear band of a Pd-based MG [14]. A weak static magnetic field is reported to suppress the diffusion of atoms in Al-rich glass forming alloy melts, which results in improvement of glass forming ability (GFA) [15]. The underlying reason was attributed to the Lorentz force generated from the magnetic field, which slowed down the atomic mobility.…”
Section: Resultsmentioning
confidence: 99%
“…When metallic flow is crossing through the magnetic field, the induced Lorentz Force (F = q v  B, where q is the charge of a particle, v is the speed and B is the intensity of magnetic field) restrains the melting flow and refines the grain size. Liu et al [45] also pointed out that Joule heating effect contributed to grain refinement. As the surface velocity of copper roller is larger, it is self-evident that the Lorentz Force on melt is stronger and imposes relatively stronger effect on crystal growth.…”
Section: Morphological Characterizationmentioning
confidence: 95%
“…Such phenomena can be explained as follows: rapid solidification inhibits crystal growth and favors crystal formation, leading to decreased grain size. From the perspective of the role of magnetic field, the re-melt metal flow can be considered as a combination of positively charged metal ions and negative electrons [45]. When metallic flow is crossing through the magnetic field, the induced Lorentz Force (F = q v  B, where q is the charge of a particle, v is the speed and B is the intensity of magnetic field) restrains the melting flow and refines the grain size.…”
Section: Morphological Characterizationmentioning
confidence: 99%